Intervention Program to Increase Self-Disclosure in Al-Muhaimin Orphanage Children - Natasya, Shafa; Anggraini, Dewi (Universitas Muhammadiyah Palembang, 2022)
An orphanage is a place for children to have rights that they don't have from their biological parents, as well as a place to communicate, to open up their selves, to get know each other, and also to build a close relationship between them. The purpose of this activity is to find out about self-disclosure to the children of the Al-Muhaimin orphanage. The subjects of this activity are children who live in Al-Muhaimin orphanage, totaling 9 people with ages ranging from 12-18 years. The data collection methods used are observation, interview, focus group discussion, and survey (pre-test) methods. The results of data collection show a lack of self-disclosure in Al-Muhaimin orphanage children. The intervention program used was psychoeducation divided into three sessions (the presentation of the material & question and answer session, filling in the wishing tree, and feedback & post-test). The provision of an intervention program in the form of psychoeducation and the activity of filling the wishing tree proved the effectiveness in increasing the self-disclosure of the children of the Al-Muhaimin Orphanage.